Emotional and Cognitive Empathy in First-Year Medical Students. (21st October 2013) - Dehning, Sandra; Gasperi, Sarah; Krause, Daniela; Meyer, Sebastian; Reiß, Eva; Burger, Max; Jacobs, Fabian; Buchheim, Anna; Müller, Norbert; Siebeck, Matthias
Abstract : Objectives . Doctors' empathy towards their patients is considered important for treatment outcome. However, during medical school there might be a decline in empathy called "hardening of the heart." This study evaluated the cognitive and emotional empathy in medical students and investigated the influence of a preference for a specialty and students attachment styles. Methods . 126 first-year medical students were included and completed the Reading the Mind in the Eyes Test revised version (RME-R), the Balanced Emotional Empathy Scale (BEES), and the Experiences in Close Relationships-Revised Adult Attachment Questionnaire (ECR-R). Results . Students identified 22 ± 4.30 of 36 photographs in the RME-R test correctly (norm: 26). The female students' mean BEES total score was 51.1 ± 17.1 and the male students' 27.2 ± 22.6 ; P < 0.0001 . The female students' mean BEES score was significantly (P = 0.0037 ) below the female norm of 60. Students who preferred a specialty with continuity of patient care scored significantly higher in the BEES (P = 0.014 ). A more avoidant attachment style was associated with a lower BEES score (P = 0.021 ). Conclusion . The students showed low emotional and cognitive empathy scores and an avoidant attachment style. This supports the inclusion of specific training in cognitive and emotional empathy in medical education.